A new genus and new species of freshwater Chaetonotidae (Gastrotricha: Chaetonotida) from Brazil with phylogenetic position inferred from nuclear and mitochondrial DNA sequences. Issue 1 (2nd January 2017) - Garraffoni, André R. S.; Araújo, Thiago Q.; Lourenço, Anete P.; Guidi, Loretta; Balsamo, Maria
Abstract : Most studies of South American freshwater Gastrotricha have focused on the inland waters of Brazil including São Paulo State, Mato Grosso do Sul State, and Pará State. In this paper, we describe a new genus and species, Cephalionotus kisielewskii gen. et. sp. nov. (Chaetonotida, Chaetonotidae), from Minas Gerais State using morphological data and DNA sequence data (18S rDNA and COI genes). The new genus contains a single psammic species collected from high altitude streams. Cephalionotus gen. nov. exhibits a set of autapomorphic characters that easily distinguish it from all other genera of Chaetonotida: extremely large cephalion and hypostomium that completely cover the dorsal and ventral sides of the head, respectively; a single pair of pleurae; peculiar shape and arrangement of dorsal and ventral scales in the posterior trunk region; one paired, very large, keeled scale at the ventral posterior end; and very long adhesive tubes divided into three parts. Affinity of Cephalionotus kisielewskii gen. et sp. nov. with other Chaetonotida (Paucitubulatina) is discussed from morphological and molecular perspectives. http://zoobank.org/urn:lsid:zoobank.org:pub:5E324696-AB33-42C2-A27A-609B1983D540